Reliability Analysis to a Satellite-Equipped Harmonic Gear Drive Subjected to Multisource Data and Imbalanced Information. (2nd July 2018) - Yang, Lechang; He, Ketai; Du, Yanhua; Guo, Yanling; Wang, Pidong
Abstract : We propose a Bayesian-based reliability framework for a satellite-equipped harmonic gear drive (HGD) mainly addressing two unsettled issues in existing research works, that is, an efficient aggregation method for multilevel system with imbalanced information and the multisource data fusion in a hierarchical structure. The proposed approach improves the estimation result for the whole system by utilizing all available information throughout the system. In particular, the heterogeneous data sets are classified into three types of collections of statistical data, time-correlated data, and performance test data based on their mathematical characteristics, respectively. Novel features include the comprehensive information aggregation approach taking into account multilevel information and a unique information-based fusion strategy. A real HGD device is demonstrated as the case study for benefit illustration and validation purpose.